2018
DOI: 10.1051/epjconf/201817605045
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric CO2 measurements with a 2-μm DIAL instrument

Abstract: We report on ground-based atmospheric concentration measurements of carbon dioxide, using a pulsed direct detection differential absorption lidar operating at 2051 nm. The transmitter is based on a tunable parametric source emitting 10-mJ energy, 10-ns duration Fourier-limited pulses. Range resolved concentration measurements have been carried out on the aerosol back-scattered signal. Cloud signals have been used to get long range integrated-path measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, the peak absorption intensity of the 1.6 μm absorption spectrum is suitable for DIAL measurements of vertical profiles in the troposphere. Some studies have suggested using the 2.0 μm band where an absorption peak line, they are limited to measure the distribution or the column amount in the range of several hundred meters due to strong absorption [ 12 , 13 , 14 , 15 ]. Moreover, although some studies have suggested using the 2.0 μm band where an off-center absorption line is usually possible to have an adaptive absorption for measurements in the troposphere [ 16 , 17 ], a 1.6 μm system benefits from a relatively lower magnitude of the absorption cross section at the center absorption line.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the peak absorption intensity of the 1.6 μm absorption spectrum is suitable for DIAL measurements of vertical profiles in the troposphere. Some studies have suggested using the 2.0 μm band where an absorption peak line, they are limited to measure the distribution or the column amount in the range of several hundred meters due to strong absorption [ 12 , 13 , 14 , 15 ]. Moreover, although some studies have suggested using the 2.0 μm band where an off-center absorption line is usually possible to have an adaptive absorption for measurements in the troposphere [ 16 , 17 ], a 1.6 μm system benefits from a relatively lower magnitude of the absorption cross section at the center absorption line.…”
Section: Introductionmentioning
confidence: 99%